Exploring therapeutic potential of mitophagy modulators using Drosophila models of Parkinson’s disease - Jyotsna Asthana; Bhupendra V. Shravage; Bhupendra V. Shravage; Bhupendra V. Shravage (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is the second most popular age-associated neurodegenerative disorder after Alzheimer’s disease. The degeneration of dopaminergic neurons, aggregation of α-synuclein (α-syn), and locomotor defects are the main characteristic features of PD. The main cause of a familial form of PD is associated with a mutation in genes such as SNCA, PINK1, Parkin, DJ-1, LRKK2, and others. Recent advances have uncovered the different underlying mechanisms of PD but the treatment of PD is still unknown due to the unavailability of effective therapies and preventive medicines in the current scenario. The pathophysiology and genetics of PD have been strongly associated with mitochondria in disease etiology. Several studies have investigated a complex molecular mechanism governing the identification and clearance of dysfunctional mitochondria from the cell, a mitochondrial quality control mechanism called mitophagy. Reduced mitophagy and mitochondrial impairment are found in both sporadic and familial PD. Pharmacologically modulating mitophagy and accelerating the removal of defective mitochondria are of common interest in developing a therapy for PD. However, despite the extensive understanding of the mitochondrial quality control pathway and its underlying mechanism, the therapeutic potential of targeting mitophagy modulation and its role in PD remains to be explored. Thus, targeting mitophagy using chemical agents and naturally occurring phytochemicals could be an emerging therapeutic strategy in PD prevention and treatment. We discuss the current research on understanding the role of mitophagy modulators in PD using Drosophila melanogaster as a model. We further explore the contribution of Drosophila in the pathophysiology of PD, and discuss comprehensive genetic analysis in flies and pharmacological drug screening to develop potential therapeutic molecules for PD.